Study of the influence of constituent ratio on the crosslinking reaction of castor oil modified epoxy resin by 4.4’-diamino diphenylmethane - Thanh, Do Minh; Hien, Le Xuan; Dung, Nguyen Tien (Vietnam Journal of Science and Technology, 2016)
The influence of the contents of epoxy resin modified by castor oil (ECO), 4,4’- diamino diphenyl methan (DDM) on the crosslinking reaction of ECO by DDM at 1800C have been studied and the mol ratio of A/E = 1, curing time of 270 min have been determined to be optimal conditions for formation of the cured coating having gel fraction, swelling degree, flexibility, adhesion, impact resistance, and relative hardness of 86%; 188 %; 1 mm, 0 point, 200 kG.cm and 0.33, respectively.